2012
DOI: 10.1093/cid/cis901
|View full text |Cite
|
Sign up to set email alerts
|

National Outbreak of Type A Foodborne Botulism Associated With a Widely Distributed Commercially Canned Hot Dog Chili Sauce

Abstract: Commercially produced hot dog chili sauce caused these cases of type A botulism. This is the first US foodborne botulism outbreak involving a commercial cannery in >30 years. Sharing of epidemiologic and laboratory findings allowed for the rapid identification of implicated food items and swift removal of potentially deadly products from the market by US food regulatory authorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…A variety of other antitoxin combinations are reported in Figure 6, including quadrivalent ABEF [43], monovalent A [48], monovalent E [18,49], and a combination of bivalent AB formulation and monovalent E formulation [50,51]. The small number of deaths from botulism reported in patients treated with these agents precludes a statistical assessment of their impact on clinical outcomes.…”
Section: Use Of Different Antitoxin Formulationsmentioning
confidence: 99%
“…A variety of other antitoxin combinations are reported in Figure 6, including quadrivalent ABEF [43], monovalent A [48], monovalent E [18,49], and a combination of bivalent AB formulation and monovalent E formulation [50,51]. The small number of deaths from botulism reported in patients treated with these agents precludes a statistical assessment of their impact on clinical outcomes.…”
Section: Use Of Different Antitoxin Formulationsmentioning
confidence: 99%
“…In the United States, Juliao et al . [79] reported that a commercially produced hot dog chili sauce seems responsible for four cases of type A botulism and Date et al . [80] reported on three outbreaks of foodborne botulism caused by unsafe canning of vegetables.…”
Section: Botulinum Neurotoxinsmentioning
confidence: 99%
“…Therefore, to avoid the production of neurotoxin, it is essential to prevent its germination. The toxin types are classified as A, B, C, D, E, F and G. Human botulism has been mainly described with the strains of C. botulinum that produce toxin types A, B and E. Botulism outbreaks caused by different home-prepared or preserved foods have been widely reported in the literature, most of them due to improperly pasteurized or packed home-canned vegetables [3,4]; home-made oil condiments and sauces [5][6][7]; fishery products [8,9]; cheese [10,11]; or meat products [12,13]. Although it is not usual, several outbreaks in table olives have also been reported to be mainly associated with black table olives [14].…”
Section: Introductionmentioning
confidence: 99%